The Effect of Credit and Market Risk on Bank Performance: Evidence from Turkey - Ekinci, Aykut (International Journal of Economics and Financial Issues, 2016)
There is a strong connection between bank performance and economic growth. Therefore, understanding on the effects of credit and market risk on bank performance could contribute to the better functioning of the banking system. This study investigates the effects of credit and market risk, i.e., interest rate and foreign exchange (FX) rate risk, on the bank performance for the Turkish banking sector in a time-varying framework employing the generalized autoregressive conditional heteroscedastic approach for the 18.01.2002-30.10.2015 period by using weekly data. The results suggest two main findings: (i) Credit risk has a negative and FX rate has a positive effect, but interest rate has insignificant effect on banking sector profitability, (ii) credit and market risk have a positive and significant effect on conditional bank stock return volatility. Keywords: Bank Lending Channel, Bank Performance, Credit Risk, Interest Rate Risk, Currency Risk JEL Classifications: C32, E43, E44